2009
DOI: 10.1136/gut.2009.177774
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of wireless capsule endoscopy in detecting small intestinal pathology in children under the age of 8 years: a multicentre European study

Abstract: Objective: To systematically evaluate the feasibility and methodology to carry out wireless capsule endoscopy (WCE) in children ,8 years to define small intestinal pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 37 publications
2
92
0
8
Order By: Relevance
“…In children, the ability and willingness to swallow endoscopic capsules can be influenced by the child's age and cognitive understanding, personality, acceptance by parents, and skill of the investigator in turning the ingestion into an interactive game 3. However, even in adolescents, up to one‐third of patients describe difficulties swallowing standard size tablets 4.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the ability and willingness to swallow endoscopic capsules can be influenced by the child's age and cognitive understanding, personality, acceptance by parents, and skill of the investigator in turning the ingestion into an interactive game 3. However, even in adolescents, up to one‐third of patients describe difficulties swallowing standard size tablets 4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is still controversial to use CE for the children under 10 years of age. Several studies described that CE has high diagnostic yield to those patients under 10 years of age (de'Angelis, 2007;Atay, 2009;Fritscher-Ravens, 2009;, and their small body size don't relate to the risk of capsule retention, which is the most serious complication in this modality as described in the latter paragraph. In addition, there was no difference in the gastric and small intestinal passage time between adult and pediatric patients .…”
Section: Agementioning
confidence: 98%
“…In addition, there was no difference in the gastric and small intestinal passage time between adult and pediatric patients . In young children (1.5-8 yr), a previous study reported CE detected small intestinal pathology in 45% (37 of 83 patients) in whom their indications are gastrointestinal bleeding, suspected Crohn's disease, abnormal pain, protein loss and malabsorption (Fritscher-Ravens, 2009). Because of no incidence of retention among those aged patients (1.5-7.9yr), CE is considered as feasible and safe down to the age of 1.5 yr. As another important aspect, swallowing of CE is unavoidable problem in small children.…”
Section: Agementioning
confidence: 98%
See 1 more Smart Citation
“…an endoscopic placement of the capsule was 1.5 years old [13][14][15]. It was reported that the endoscopic replacement into the stomach with polyp snare was performed in a 42-month-old girl in Korea [16].…”
Section: The Procedures Of Cementioning
confidence: 99%